2012
DOI: 10.1016/j.cellsig.2011.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide kinase regulates TNFα-stimulated NADPH oxidase activity and eicosanoid biosynthesis in neuroblastoma cells

Abstract: A persistent inflammatory reaction is a hallmark of chronic and acute pathologies in the central nervous system (CNS) and greatly exacerbates neuronal degeneration. The proinflammatory cytokine tumor necrosis factor alpha (TNFα) plays a pivotal role in the initiation and progression of inflammatory processes provoking oxidative stress, eicosanoid biosynthesis, and the production of bioactive lipids. We established in neuronal cells that TNFα exposure dramatically increased Mg2+-dependent neutral sphingomyelina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…This finding is particularly relevant when considering that macrophages play critical roles in chronic and acute inflammation and that these cells facilitate cancer cell migration (21,46). In addition, Barth et al (4) recently showed that ceramide kinase, the enzyme responsible for the phosphorylation of ceramide to C1P, regulates NADPH oxidase activity and eicosanoid biosynthesis in neuroblastoma cells, an action that is consistent with our recent finding that C1P increases the production of reactive oxygen species through activation of NADPH oxidase in macrophages (2). Besides these proinflammatory actions, increasing evidence suggests that C1P can aslo function as an anti-inflammatory agent under different experimental settings.…”
mentioning
confidence: 99%
“…This finding is particularly relevant when considering that macrophages play critical roles in chronic and acute inflammation and that these cells facilitate cancer cell migration (21,46). In addition, Barth et al (4) recently showed that ceramide kinase, the enzyme responsible for the phosphorylation of ceramide to C1P, regulates NADPH oxidase activity and eicosanoid biosynthesis in neuroblastoma cells, an action that is consistent with our recent finding that C1P increases the production of reactive oxygen species through activation of NADPH oxidase in macrophages (2). Besides these proinflammatory actions, increasing evidence suggests that C1P can aslo function as an anti-inflammatory agent under different experimental settings.…”
mentioning
confidence: 99%
“…32 Both Ab and TNFa activate neutral sphingomyelinase generating ceramide and significantly changing the lipid raft environment. 21,33 Such changes could contribute to the proposed signaling pathway by altering interactions between raft components.…”
mentioning
confidence: 99%
“…Subsequent studies by the same group demonstrated that C1P, the product of CerK, was a direct activator of cytosolic phospholipase A 2 [ 21 ], a major enzyme responsible for the regulation of arachidonic acid release in mammalian cells, and that eicosanoid levels were lower in primary mouse embryonic fibroblasts isolated from CerK knockout mice [ 22 ]. Moreover, depleting CerK activity using either specific siRNA to silence the gene encoding this kinase or the pharmacological inhibitor NVP-231 completely blocked eicosanoid biosynthesis [ 23 ]. Additionally, we show here that CerK-deficient cells cause potent reduction in the protein levels of the crucial adipogenesis marker PPAR γ , which is both necessary and sufficient for adipocyte differentiation [ 24 ], thereby suggesting that the loss of CerK might be detrimental for optimal adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 99%